The body as a cultural resource for entrepreneurs in stigmatized settings: The case of sex toys by women for women - Bojovic, Neva; Garud, Raghu; Cheded, Mohammed (Journal of Business Venturing, 2025)
Entrepreneurs seeking legitimacy for their stigmatized products with mainstream audiences must deploy strategies to redefine their products' cultural significance. This paper investigates how the body, often a focal point of stigma, serves as the foundation for these strategies. Through an analysis of exemplary cases in the sex toy industry, we identify three strategies—visibilizing, obfuscating, and transforming—used by entrepreneurs to deal with different sources of stigma, including tribal stigma, blemishes, and abominations associated with the products. Our findings provide novel insights into the role of the body in entrepreneurial strategies to tackle stigma and gain legitimacy for their products, thereby contributing to the literatures on entrepreneurship in stigmatized settings and cultural entrepreneurship.